Theoretical Analysis of a Potentiostat for Studying Microbial Fuel Cells - Marques, Catarina Lousa (2022)
For many years, Microbial Fuel Cells (MFCs) have been developed as alternatives for generating electricity via the oxidation of organic matter by bacteria. Even though individual MFC units are low in power, significant progress has been achieved in terms of MFC material and configurations, enabling them to generate higher output levels. Nonetheless, MFCs are are mainly produced using conventional laboratory methods that can take up to several months to bring the MFCs to their maximum power aptitudes. In this dissertation, an approach to use a low-cost potentiostat was developed in order to study MFCs comportament. Initially, the work focused on establishing an interface on Node-RED and an interconnection between the living cells in the MFC. In order to achieve that, was used a mbed NXP LPC1768 microcontroller to communicate with the interface created and also with the potentiostat. To fully explore the potentiostat, were studied several electrochemical tests possible to execute in the MFC reactor and the expected results. Finally, is possible to say that the potentiostat is fast, produces low noise and is a versatile instrument, very promising in the study of this emerging renewable energy like is MFCs.